Effect of Defoliation at Different Stages on Grain Sorghum - K. L. Roozeboom; B. Owuoche (Kansas Agricultural Experiment Station Research Reports, 2023)
Loss of leaf area usually results in yield loss in grain crops, but the amount of yield loss varies with extent and timing of defoliation. Grass crops, such as corn and grain sorghum, are particularly sensitive to leaf area loss near the time of seed set because there is little opportunity for the plant to compensate. An experiment to quantify yield reductions associated with various levels of defoliation imposed at different stages of grain sorghum development was conducted at Manhattan, KS, in 2022. Target defoliations of 0, 33, 66, and 100% were imposed at 5-leaf, flag-leaf-appearance, half-bloom, and hard-dough stages. Defoliation of 5-leaf sorghum resulted in minimal yield loss unless the defoliation rate was 100%, which delayed heading and reduced head size and seed size. Leaf area losses of 50% or more at the hard dough stage caused yield reductions of only about 10–12%. Yield reductions were greatest when leaf area was lost at flag leaf appearance or half bloom. Leaf area loss of 60% and 100% caused yield losses of 25% and 75%, respectively. These yield losses were associated with different combinations of reductions in head size and seed size.
Keywords: grain sorghum; defoliation; grain yield; yield components